UNDERSTANDING WASATHIYYAH IN THE BOOK OF AL-QUR’AN AL-KARIM DAN TERJEMAHAN BEBAS BERSAJAK DALAM BAHASA ACEH - Fauzi, Fauzi (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2021)
Abstract: This article aims to examine the meaning of wasathiyyah in the book al-Quran al-Karim dan Terjemahan Bebas Bersajak dalam Bahasa Aceh. The research is qualitative and documentation as a data collection technique. The result of the research is that the author of this book gives varied meanings with the word wasatha. Among them the meaning of this word: saban (same), sama teungoh (same in the middle), seudang (middle). Wasathiyyah covers aspects of worship, mu‘âmalah, ethics and so on. In terms of worship, levels, models and times are given guidance in the Shari‘ah. In the aspect of mu‘âmalah, this concept regulates how to communicate, time and how to interact. In terms of ethics, this wasathiyyah becomes a role model in attitude and behavior.Keywords: meaning, wasathiyyah, book of Mahjiddin Jusuf, life